CEO-speeches and stock returns - Christina E. Bannier; Thomas Pauls; Andreas Walter (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We analyze the market reaction to the sentiment of the CEO speech at the Annual General Meeting (AGM). Adapting a finance-specific German dictionary based on Loughran and McDonald (2011), we find that CEO speeches' textual sentiment is significantly related to abnormal stock returns and trading volume around the AGM. Investors hence seem to perceive the speeches' sentiment as a valuable indicator of future firm performance.
Keywords: G02; G12; G14; 330